Penerapan Pembelajaran Ilmu Tajwid untuk Meningkatan Kemampuan Membaca Al-Qur’an di Madrasah Diniyah Mamba’ul ‘Ulum Sekuwung Kedungbanteng - Nurjanah, Siti; Muqorrobin, Syamsul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Al-Qur'an is something very noble, it should not be read carelessly, but there are rules about reading the Al-Qur'an that have been taught in the science of recitation. Reading the Al-Qur'an using tajwid knowledge is the main requirement for reading the Al-Qur'an to be precise and correct. Most of the Madrasah Diniyah Mamba'ul 'Ulum Sekuwung students read the Al-Qur'an fluently, but there are still some errors in implementing the reading law, therefore more intense guidance is still needed. This research aims to determine the extent of the application of tajwid science in improving the ability to read the Al-Qur'an at Madrasah Diniyah Mamba'ul 'Ulum Sekuwung. This research uses a qualitative approach with the type of field research. Data collection techniques use observation, interviews and documentation. The results of the research show that by learning the science of tajwid, Madrasah Diniyah Mamba'ul 'Ulum students are able to apply the science of tajwid in reading the Al-Quran, to measure the extent to which students apply the science of tajwid learning, they can measure it at the time of deposit according to their respective class volumes, the teacher provides additional material to increase students' understanding of the science of recitation